A Study of The Quality of Cement Sand Mix in Sandcrete Block Moulding in Ondo State Nigeria - Ayodele, Elijah; AKINMUSIRE, Adeleye O.; WILLIAMS, Samuel O.; OLOFINSAWE, Moses O.; OLOGUNAGBA, Modupe M.; OGUNBODE, Benson A.; ALABI, Michael O (Advances in Social Sciences Research Journal, 2021)
This study determined the quality of the mix ratio of sand and cement in sandcrete block in Ondo State of Nigeria. This involved the determination of number of headpans of sand that are mixed with one headpan of cement and the ratio of cement sand mix in sandcrete blocks produced in Ondo State. This study was carried out through interview of labourers at the 90 spots of block moulding in Ondo State. Thirty spots were taken each of the three senatorial districts in Ondo State. The study showed the cement sand mix ratio to be 1:11. This implies that there is 83% increase of sand in the mix above the standard. Very weak sandcrete blocks have arisen from this mix ratio over the years and must have contributed to the incessant building collapses. The followings are the recommendations: Sandcrete blocks should be made on the site in an approved machine to be provided by the contractor or an approved supplier and should have a minimum crushing strength of 273.4 tonner per square of gross area at 28 days in case of hollow blockwork. The blocks should be composed of 1:6 cement and sand measured by volume unless otherwise specified or directed on the site, turned three times until an even colour and consistency occur throughout. Water should be added gently from a watering can through a rose, the quantity of water added being just sufficient to secure cohesion. After wetting, the mixture shall be turned over three times and well rammed into moulds and smoothed from the machine on pellets, the blocks should be made to mature under shade in different rows, one block high, with a space between each block and for at least 24 hours. Then they should not be stacked up or removed from shade for at least a further 7 days then stacked up not more than 5 blocks high in shade for a minimum of 14 days. No block should be built into any part of the building until they have been cured for at least 14 days. The faces of blocks except where otherwise described should be left rough for plastering. The concrete blocks generally shall be 450 mm long, 225mm or 150mm deep and of the required thickness. Keywords: Cement, Sand, Cement Sand Mix, Sandcrete Block, Ondo State Nigeria.